Individual airborne PCB congeners effective volumes measured in 27 samples using polyurethane foam passive air samplers (PUF-PAS) from Portland, OR, 2022 - Alexis Slade; Andres Martinez; Martine Mathieu-Campbell; Shannon Watkins; Cassie Cohen; Keri C Hornbuckle (PANGAEA, 2025)
We provide individual PCB congener airborne concentration data for 27 samples collected from 21 locations in 2022 at the Portland Harbor Superfund site and surrounding areas in Portland, OR, USA. Measurements were obtained using polyurethane foam passive air samplers (PUF-PAS) deployed for 43 days. Masses of individual PCB congeners measured in each PUF-PAS sample are included, along with masses from 12 laboratory blanks. Estimated effective volumes used to calculate airborne PCB concentrations from the collected masses are also reported. Additionally, PCB water emissions from the Portland Harbor for individual congeners were calculated using EPA-provided water concentration data from 2018.
In: Slade, A et al. (2025): Airborne polychlorinated biphenyl congener concentrations using PUF-PAS from the Portland Harbor Superfund Site, Portland, OR, 2022 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.983837